Pediatric Idiopathic Inflammatory Myopathies: An Update on Diagnostic and Treatment Strategies - Muller-Felber, Wolfgang; Wanschitz, Julia; Vill, Katharina; Baumann, Matthias (Neuropediatrics, 2013)
Diagnostic approach and treatment of idiopathic inflammatory myopathies have changed considerably during the past decades. In this review, new insights in the pathogenesis, the role of muscle biopsy, and magnetic resonance imaging in the diagnostic process in children with suspected myositis are discussed. Current treatment strategies and complication management is described in detail.
Keywords: inflammatory myopathies; juvenile dermatomyositis; children; muscle biopsy